States of drunkenness: bar-life in Istanbul between empire, occupation, and republic, 1918–1923. Issue 2 (13th January 2021) - MacArthur-Seal, Daniel-Joseph
Abstract: The article examines the operation of the multiple regimes of alcohol control formulated by Istanbul's Allied, Ottoman, and Turkish Nationalist authorities that distinguish the period 1918-1923 and their impact on alcohol entrepreneurs and drinkers. By combining Allied and Ottoman police and newspaper reports and the personnel testimony of soldiers, officials, and civilians in the occupied city, the article supplements the small existing literature on Turkish prohibition, which has been mostly focused on the debate in the Grand National Assembly in Ankara and neglects the impact of restrictions and eventual prohibition of alcohol on its sellers and consumers in Istanbul.